Clients and service providers' assessment of Public and Non-Governmental Youth-Friendly Health Services in Lagos Nigeria: A mixed method approach - Toriola Femi-Adebayo; Olusola Adejumo; Bisola Adebayo; Andrew Ariauhi; Victor Adepoju (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2019)
Background: The World Health Organization prescribed that Youth-Friendly health services must be accessible, acceptable, equitable, efficient, effective, comprehensive and appropriate to meet the health needs of young people. Objective: To compare the clients' and service providers' assessment of services offered at the public and Non-Governmental Organization (NGO) Youth Friendly facilities (YFF) in Lagos Nigeria. Methods: A mixed method approach was used. Structured questionnaires were administered on youths (294 from public and 273 from NGO YFF) from ten (5 public and 5 NGO) YFF. Ten key informant interviews with service providers were also conducted between March 1st and December 31st 2014. SPSS version 22 was used to analyze quantitative data while thematic analysis of interviews with service providers was done. Results: Youths who utilized the public YFF had 60% chance (AOR 1.6, 95%CI 1.3 - 2.5, p= 0.005) of experiencing longer waiting times, 80% chance (AOR 1.8, 95%CI 1.2 - 2.8, p=0.004) of being counseled in a separate room and over two-fold chance (AOR 2.3, 95%CI 1.7 - 3.3, p <0.001) of having free services. Sexual and reproductive health was the major complaint area of the youths while funding was the major challenge of service providers at both the public and NGO YFF. Conclusion: To address the needs of the youths, there is a need to provide more funds and provide necessary logistics required by YFF.